Analisis Penerapan Strategi dan Metode Pembelajaran Guru:Studi Kualitatif di SDN 1 Gobras - Sunanih Sunanih; Adrian Nurul Arifin; Ahmad Zidan Sulaeman; Dwiky Novaldi Ramdhani; Rani Nur’aeni; Chalifa Chairunnisa; ⁠Desti Rahmasari; Ghaida Putri Adella; Alipia Oktapiani; Herna Aulia; M Fajar Nurdiansyah; Rara Nurrahmah (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to examine the implementation of teaching strategies and methods at SDN 1 Gobras using a qualitative approach supported by NVivo 15 software. Data were collected through in-depth interviews, direct observations, and documentation to evaluate the effectiveness of student-centered learning methods, such as a modified Problem-Based Learning (PBL) approach. The findings reveal that kinesthetic strategies significantly enhance students’ learning enthusiasm, particularly in lower grades (grades 1-3). However, the study also identifies key challenges, including limited learning resources and time allocation. To address these issues, continuous teacher training and improved learning facilities are recommended. These findings are expected to serve as practical guidance for elementary schools in enhancing the quality of learning effectively.